2015
DOI: 10.1371/journal.pone.0135467
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Lactococcal Drug Dependent Transcriptional Regulator LmrR to Its Ligands and Responsive Promoter Regions

Abstract: The heterodimeric ABC transporter LmrCD from Lactococcus lactis is able to extrude several different toxic compounds from the cell, fulfilling a role in the intrinsic and induced drug resistance. The expression of the lmrCD genes is regulated by the multi-drug binding repressor LmrR, which also binds to its own promoter to autoregulate its own expression. Previously, we reported the crystal structure of LmrR in the presence and absence of the drugs Hoechst 33342 and daunomycin. Analysis of the mechanism how dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
(36 reference statements)
3
32
0
Order By: Relevance
“…Thus, a PadR dimer binds two effector molecules with a 1:2 stoichiometry ( Supplementary Figure S15A ). In contrast, LmrR, a member of the PadR subfamily-2, contains only one domain consisting of α1-α4 helices and a β-stranded wing and thus lacks the interdomain pocket observed in PadR ( Supplementary Figures S14A and 15B ) ( 19 , 22 ). Instead, LmrR has exceptionally long terminal helices, α1 and α4, which provide the dimerization interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a PadR dimer binds two effector molecules with a 1:2 stoichiometry ( Supplementary Figure S15A ). In contrast, LmrR, a member of the PadR subfamily-2, contains only one domain consisting of α1-α4 helices and a β-stranded wing and thus lacks the interdomain pocket observed in PadR ( Supplementary Figures S14A and 15B ) ( 19 , 22 ). Instead, LmrR has exceptionally long terminal helices, α1 and α4, which provide the dimerization interface.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the discovery of a growing number of PadR family members and the increasing interest in their critical functions, the structural basis of effector-mediated gene regulation is poorly understood in the PadR family because of the highly limited structural information concerning the interactions of PadR family members with effectors and operator DNAs. The structure of LmrR, a subfamily-2 member, in complex with its effectors was solely characterized in bacteria ( 19 , 22 ). LmrR contains a pocket between the two subunits of the LmrR dimer where it binds an effector molecule.…”
Section: Introductionmentioning
confidence: 99%
“…S1) 15, 16 . In the previous study, we demonstrated that LmrR exists as a conformational ensemble with multiple α4 helix orientations in solution (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…16 This hydrophobic pore serves as a promiscuous binding pocket where planar aromatic molecules bind, as shown in X-ray and NMR structures of LmrR with various planar drugs bound. [16][17][18] Two tryptophan residues, one from each subunit, i.e., W96 and W96', play a key role in binding by sandwiching the guest molecule via π-stacking interactions. Previously, we have shown that this arrangement is attractive for the supramolecular self-assembly of a novel artificial metalloenzyme, by combining the protein LmrR with a Cu(II) complex with a planar aromatic ligand, like 1,10phenanthroline (phen) ( Fig.…”
Section: Main Textmentioning
confidence: 99%